Quantitative Analysis of Cytokine-Induced Hepatocyte Nuclear Factor-4α Phosphorylation by Mass Spectrometry - Wang, Zhongyan (2011)
Hepatocyte nuclear factor-4α (HNF-4α), a liver-enriched transcription factor, is essential for liver development and function. HNF-4α regulates a large number of liver-specific genes, many of which are modulated by injury. While HNF-4α function is regulated by phosphorylation, only a limited number of phosphorylation sites in HNF-4α have been identified, and the roles of HNF-4α phosphorylation after injury are unexplored. To address these issues, we have carried out an extensive quantitative mass spectrometry (MS)-based analysis of HNF-4α serine and threonine phosphorylation in response to cytokine stimulation. Studies were performed in HNF-4α-enriched HepG2 cells treated with cytokines for 3 h or left untreated, followed by chemical derivatization of the phosphoserine and phosphothreonine residues using stable isotopic variants of dithiothreitol (DTT) and MS analysis. This has allowed the identification and relative quantification of 12 serine/threonine phosphorylation sites in HNF-4α. Eight of these phosphorylation sites and their sensitivity to cytokine stimulation have not been previously reported. We found that cytokine treatment leads to an increase ofHNF-4α phosphorylation in several phosphopeptides. The phosphorylation of HNF-4α mediated by protein kinase A (PKA) significantly reduces HNF-4α binding activity, which mimics the repressive effect of cytokines on HNF-4α binding, and the inhibition of PKA activity by PKA inhibitor can partially recover the reduced HNF-4α binding activity induced by cytokines. These results suggest that the mechanism that alters HNF-4α binding after cytokine stimulation involves modulation of specific HNF-4α phosphorylation dependent, in part, on a PKA signaling pathway. [Image: see text]